The administrators of the Kraśnik provostship of Canons Regular of the Lateran from its foundation to its reform in 1628 - Łatak, Kazimierz (Saeculum Christianum. Pismo Historyczne, 2021)
Summary This article focuses on the provostship of the monastery of the Canons Regular of the Lateran in Kraśnik from its foundation in May 1468 to the reform of 1620-1627. Founded by Jan Rabsztynski of Tęczyn, the owner of the Kraśnik estate, the convent was considered as a prominent center of religious, social, and cultural activity in the Lublin Region. Therefore, studying its history, culture, and religious activity is important in understanding the history of the town and the region. The culture of the monastery influenced the culture of the local environment, while the culture of the surrounding area left its traces in the culture and activities of the convent.